Unravelling the Swear Words Uttered by the Characters in Suicide Squad Movie from Pragmatic Perspective - Gabriella Kristina Handayani; Endar Rachmawaty Linuwih; Eka Fadilah (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2023)
Nowadays, the use of profanity is becoming more widespread, and it seems to be particularly common among teenagers. However, swear words do not have a fixed, universal meaning, as their usage is context-dependent and pragmatic. A single swear word can have multiple meanings and functions depending on the situation. This study aims analyze the pragmatic purposes behind their usage, based on the themes proposed by Ljung in 2011. The research adopts a qualitative content analysis method since the data comprises the characters' spoken words in the movie. The data collection process involves gathering relevant information about swear words, and once sufficient material is obtained, the movie is rented from YouTube. The data analysis steps involve data reduction, data displaying, and finally drawing conclusion. The findings reveal that the functions of the swear words, replacive swearing emerges as the most frequently used function among the characters, followed by name-calling, and the third are expletive interjection, and emphasis with the same occurrence frequency, anaphoric use of epithet, adjectives of dislike, and the last are unfriendly suggestions, as well as adverbial/adjectival intensifiers which share the same occurrence frequency. The results indicate that swear words are heavily used in the Suicide Squad movie. This research provides a rich theoretical and empirical framework for future research, especially concerning the study of swear words.